Reassessing Child Welfare in Islamic Jurisprudence: The Abrogation of Guardianship According to Al-Būṭī’s Maslahah Theory - Aljurjani, Muhammad; Mujib, Lalu Supriadi; Sainun, Sainun (DIKTUM: Jurnal Syariah dan Hukum, 2025)
Background: In numerous Muslim-majority nations, paternal guardianship rights over girls are frequently maintained, despite evidence of the fathers' negligence of their duties. This prompts essential inquiries regarding the equilibrium Islamic legal systems must maintain between father power and child care Purpose: This paper examines the legitimacy of designating inattentive fathers as walī nikāḥ (marriage guardians) in accordance with Islamic law, utilizing Sa‘īd Ramadān al-Būṭī’s maslahah theory as the primary analytical framework Methods: This research utilizes a normative-comparative legal method to analyze classical Islamic law, Indonesia's Compilation of Islamic Law (KHI), and pertinent provisions in Tunisia's Code of Personal Status and Morocco's Mudawwanah Results: Research indicates that al-Būṭī’s quintuple criteria of maslahah—comprising its congruence with maqāṣid al-sharīʿah, the Qur’an, Sunnah, qiyās, and a hierarchy of benefits—can substantiate the revocation of guardianship powers from negligent fathers and their reassignment to judicial authorities. The research illustrates that this principle-based, textually anchored paradigm upholds both legal integrity and child protection. Implication: Theoretically, the research redefines maslahah as an instrument for reform within conservative legal frameworks, while practically, it advocates for legal systems such as Indonesia's to implement more explicit statutory exclusions and child-focused policies. Originality: This study's originality is in its conservative yet reformist interpretation of maslahah, demonstrating that legal reform is both feasible and essential for upholding justice and ethical oversight within Islamic family law, even within a traditionalist context